External validation of N2H3 nomogram to predict outcomes in patients with acute ischemic stroke treated by intravenous thrombolysis - Huai-Mei Zhang; Zi-Duo Shen; Yang Qu; Peng Zhang; Reziya Abuduxukuer; Li-Juan Wang; Yu Li; Yu-Mei Chen; An-Ran Liu; Xiao-Dong Liu; Li-Li Zhao; Chun-Yu Yang; et al. (Brain Circulation)
BACKGROUND: The N2H3 model was evaluated for forecasting the 3-month outcomes for patients experiencing acute ischemic stroke who received intravenous thrombolysis (IVT), in our previous study. The present study aimed to validate the predictive ability of the N2H3 model and to compare its accuracy to the THRIVE-c and START models (both of which are widely employed for prognostic predictions following IVT). METHODS: Our study prospectively enrolled consecutive stroke patients who received IVT from 16 hospitals. Cases from one hospital were included in External Validation Dataset 1, whereas External Validation Dataset 2 included patients from the other 15 hospitals. The effectiveness of each model in distinguishing outcomes was assessed by calculating the area under the receiver operating characteristic curve (AUC-ROC). In addition, the overall performance of the N2H3 model was assessed through the scaled Brier score. RESULTS: Finally, 794 patients were included, of which 582 were included in External Validation Dataset 1 and 212 in External Validation Dataset 2. The N2H3 model’s AUC-ROC for forecasting unfavorable outcomes at 3-months was 0.810 (95% confidence interval [CI]: 0.771–0.848) in the first dataset and 0.782 (95% CI: 0.699–0.863) in the second dataset. For the START model, the AUC-ROCs in the two validation datasets were 0.729 (95% CI: 0.685–0.772) and 0.731 (95% CI: 0.649–0.772), respectively. The THRIVE-c model showed AUC-ROCs of 0.726 (95% CI: 0.682–0.770) and 0.666 (95% CI: 0.573–0.759), respectively. The Brier scores of the N2H3 model were 0.153 and 0.147 in cohorts 1 and 2, respectively. CONCLUSIONS: The N2H3 model exhibited good predictive ability in both external validation cohorts. Moreover, it demonstrated advantages over the THRIVE-c and is not inferior to the START nomogram in this regard. TRIAL REGISTRATION: Clinical Research of Intravenous Thrombolysis for Ischemic Stroke in Northeast of China (CRISTINA) (identifier: NCT05028868).